A TRACER STUDY OF BATANGAS STATE UNIVERSITY (BATSTATEU)- LIPA CITY GRADUATES OF SY 2017 – 2018 - Malaluan, Nerrie E.; Godoy, Michael C.; Balazon, Francis G.; Soquiat, Monette M.; Balita, Lourdes (International Journal of Research -GRANTHAALAYAH, 2020)
This study aimed to determine the employability of Batangas State University-Lipa City graduates within two (2) years after graduation. In this tracer study the BatStateU-Lipa City graduates of School Year 2017 -2018 are the participants. To obtain the needed information, the researchers used online survey to be filled in by the graduates. The survey questionnaire served as the data gathering instrument. The subjects of the study were 454 graduates whose names were drawn randomly from the master list of 514 graduates of the four colleges offering different academic programs. Findings of the study revealed that almost all of the BatStateU-Lipa City graduates are currently employed and working in a full time basis. On the other hand, more than half are holding permanent position. However, most of them are not yet pursuing masters’ degree or post graduate studies. The developed alumni directory will help the University in tracking the alumni and to easily collect and update the personal and professional information of graduates. It is recommended that the graduates may pursue professional development and advancement by taking masters’ degree or advance study for them to upgrade their core competencies and land in a job that will provide vast opportunities to practice their profession. The expansion of tie-ups with public and private agencies and enterprises that can provide employment opportunities to the University graduates be a continuing process in all colleges to maintain the higher rate of employability. Further study may be conducted focusing on the relevance and responsiveness of the different programs.